The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1007/s13410-021-01033-4
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a diabetes educational intervention at primary school

Abstract: Background Brazil ranks fifth in the world in the number of adults with diabetes, and third for type 1 diabetes. Conducting educational actions on this topic in public schools in this country is extremely important, since it can assist in the early adoption of good life habits and in a better care for students in this condition.Objective The aim of this study was to assess the effectiveness of an educational intervention about diabetes for students and school staff. Methods This is an interventional non-random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…As dificuldades de manejo do DM1 na escola justificam a necessidade de desenvolver estratégias que promovam a saúde e a qualidade de vida no ambiente escolar frente ao DM1. Nesse contexto destacamos a importância da promoção lúdica da educação em diabetes para o público infanto-juvenil dentro das escolas, como no caso do material desenvolvido pelo programa KiDS (IDF, 2019b) bem como o treinamento das equipes escolares, que já vem sendo realizado pelos Centro de Referência Diabetes nas Escolas (REIS et al, 2018;MOURÃO et al, 2022). Essas ações visam tornar a escola um ambiente mais seguro e acolhedor (BECHARA et al, 2018), onde os colegas e funcionários possam ser uma fonte de apoio e suporte para crianças e adolescentes com DM1.…”
Section: Discussionunclassified
“…As dificuldades de manejo do DM1 na escola justificam a necessidade de desenvolver estratégias que promovam a saúde e a qualidade de vida no ambiente escolar frente ao DM1. Nesse contexto destacamos a importância da promoção lúdica da educação em diabetes para o público infanto-juvenil dentro das escolas, como no caso do material desenvolvido pelo programa KiDS (IDF, 2019b) bem como o treinamento das equipes escolares, que já vem sendo realizado pelos Centro de Referência Diabetes nas Escolas (REIS et al, 2018;MOURÃO et al, 2022). Essas ações visam tornar a escola um ambiente mais seguro e acolhedor (BECHARA et al, 2018), onde os colegas e funcionários possam ser uma fonte de apoio e suporte para crianças e adolescentes com DM1.…”
Section: Discussionunclassified
“…In Spain, only 36.9 percent of the surveyed teachers had sufficient basic knowledge about diabetes. Nonetheless, other studies strongly advocated for a training program for teachers to improve their diabetes knowledge after observing relatively low levels of knowledge (23,24) .…”
Section: Discussionmentioning
confidence: 99%
“…The Brazilian study also promoted health education in public schools and evaluated the effectiveness of diabetes interventions in the school environment. This study led to essential changes in the knowledge and perceptions of students, with significant changes related to hypoglycemia and sugar intake by people with diabetes [8].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that children and teenagers with T1DM experience shame and embarrassment when administering insulin and checking their blood sugar levels, both inside and outside of schools. Since numerous daily doses of insulin have long been an effective T1DM treatment, it is typically necessary to apply at least one dosage at school, particularly before meals [8].. Patients with diabetes who did physical activities and exercise got better results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation